Hubungan Tingkat Pengetahuan dan Sikap terhadap Perilaku Perawatan Kebersihan Organ Reproduksi pada Saat Menstruasi Siswi SMAN 1 Belopa - Fitriani Abdal; Miftahul Jannah; Purnama Putri Syamsuddin (STIKES Columbia Asia Medan, 2024)
Relations rate of Knowledge and Attitudes toward Organ Reproductive Behaviour Hygiene Care during menstruation Students SMK 3 Pare Pare, guided. Hygiene reproductive organ is a state of sexual organs free from dirt and infection. Maintain the cleanliness of the reproductive organs during menstruation is how to maintain the cleanliness of the sexual organs or reproductive organs during menstruation to be free from an infection and disease (Laila, 2011). The purpose of this study was to determine the relationship of the level of knowledge and attitude towards hygiene behavior reproductive organs during menstruation SMK N 3 Pare Pare. This research is analytic cross sectional study. The location study was conducted in SMK N 3 Pare Pare. As for the research was conducted in April-May 2024. Its population is a class X (ten) majoring in dressmaking and beauty with the sampling method is simple random sampling with 48 samples. The results showed no relationship between the level of knowledge and attitude towards hygiene behavior reproductive organs during menstruation using chi square test was obtained p-value (Value) = 0.658 with significance level of 5%, as the value of p = 0.658> 0.05. And the attitude obtained p value (value) = 0.658 with significance level of 5%, as the value of P = 0.337> 0.05. Based on the research results obtained, the researcher expects good cooperation between educational institutions and parents in order to provide knowledge on how to keep kebersihaan reproductive organs during menstruation correct.